Patent foramen ovale and cryptogenic stroke: diagnosis and updates in secondary stroke prevention - Yuan, Kristy (Stroke Vasc Neurol, 2018)
The patent foramen ovale (PFO), given its high prevalence in the general population and especially in patients with cryptogenic stroke, has long generated investigation and debate on its propensity for stroke by paradoxical embolism and its management for stroke prevention. The pendulum has swung for percutaneous PFO closure for secondary stroke prevention in cryptogenic stroke. Based on a review of current evidence, the benefit from PFO closure relies on careful patient selection: those under the age of 60 years with few to no vascular risk factors and embolic-appearing stroke deemed cryptogenic after thorough evaluation. As these data look towards influencing guideline statements and device approvals in the future, patient selection remains the crucial ingredient for clinical decision making and future trials.